Internet of things for facility management strategies of service optimization and innovation - Atta, Nazly (Springer, 2021)
This book proposes strategies for FM services optimization and innovation, based on innovative models of IoT application and big data management within FM processes, able to support FM stakeholders in: orienting and managing big data flows and their sources (sensor, RFID, etc.); changing FM services demand/offer and developing new approaches to FM agreements; drawing new supply chains based on network approaches; and outlining new profiles of competences for FM stakeholders. The book demonstrates that FM stakeholders (e.g. Real Estate owners, FM providers, service suppliers, etc.) increasingly need new support tools for understanding the features of the current offer of innovative ICT solutions in order to become promoters of FM innovation, and it provides them with an analytical-procedural framework useful for defining and implementing IoT-based FM services.